PENGARUH BIAYA PEMELIHARAAN (MU’NAH) TERHADAP KEPUASAN NASABAH DALAM MENGGADAIKAN EMAS (STUDI KASUS: UNIT PEGADAIAN SYARIAH MANGGIS KOTA BUKITTINGGI) - Diana Ferta; Novera Martilova (CV. Adiba Aisha Amira, 2023)
The purpose of this research was to find out whether there is and how big is the influence of maintenance costs (Mu'nah) on customer satisfaction in pawning gold at the Manggis Syariah Pawnshop Unit, Bukittinggi City. This research can be used to increase customer satisfaction in gold pawning in the future. The type of research used in this research is descriptive quantitative research with a quantitative approach and a type of field research using a questionnaire (Likert scale) and a total sample of 81 respondents. And with the method of data analysis used validity, reliability, classic assumptions (normality test, autocorrelation test), simple linear regression test, hypothesis test (t test), and test the coefficient of determination R². The results of this study indicate that the regression coefficient has a value of 0.544 if each increase of 1 unit of work discipline variable will affect the satisfaction of the pilgrims by 0.544. Then, the calculated t value = 10.109 which is greater than t table = 1.994 (10.109 > 1.994) and a sig of 0.000 <0.05. This indicates that H₁ is accepted or H₀ is rejected. And the results of the R² test obtained a value of 0.564 or 56.4%. Which proves that a large number of independent variables can explain the dependent variable with a figure of 56.4% and the remaining 44% is explained by other variables. Based on the t test, the cost of Mu'nah partially has a significant effect on Customer Satisfaction of Gold Pawning at the Manggis Syariah Pawnshop Unit, Bukittinggi City.